1999
DOI: 10.1074/jbc.274.14.9409
|View full text |Cite
|
Sign up to set email alerts
|

A Region in IVS5 of the Human Cardiac L-type Calcium Channel Is Required for the Use-dependent Block by Phenylalkylamines and Benzothiazepines

Abstract: Mutations in motif IVS5 and IVS6 of the human cardiac calcium channel were made using homologous residues from the rat brain sodium channel 2a.[ 3 H]PN200-110 and allosteric binding assays revealed that the dihydropyridine and benzothiazepine receptor sites maintained normal coupling in the chimeric mutant channels. Whole cell voltage clamp recording from Xenopus oocytes showed a dramatically slowed inactivation and a complete loss of use-dependent block for mutations in the cytoplasmic connecting link to IVS5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
4
29
2
Order By: Relevance
“…A comparison of the PAA sensitivities of Ca v 2.1 mutants and chimeric channel constructs inactivating at different rates revealed a strong correlation between the rates of fast voltage-dependent inactivation and apparent PAA sensitivities. [11][12][13] Similar findings were reported for Ca 2ϩ channel block by diltiazem. 11,14 Subsequently, the studies concentrated on the localization of inactivation determinants that are relevant for channel inhibition.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…A comparison of the PAA sensitivities of Ca v 2.1 mutants and chimeric channel constructs inactivating at different rates revealed a strong correlation between the rates of fast voltage-dependent inactivation and apparent PAA sensitivities. [11][12][13] Similar findings were reported for Ca 2ϩ channel block by diltiazem. 11,14 Subsequently, the studies concentrated on the localization of inactivation determinants that are relevant for channel inhibition.…”
supporting
confidence: 79%
“…[2][3][4]6 Since then, numerous studies in myocardial and smooth muscle cells have shown that Ca 2ϩ channel inhibition by these compounds, as well as by the new compound mibefradil, reflect a balance between channel shut-off during membrane depolarization and subsequent recovery at rest. [7][8][9][10][11] Over the last three years there has been substantial progress toward understanding the role of inactivation in Ca 2ϩ channel inhibition by Ca 2ϩ antagonists. Site directed mutagenesis enabled a detailed analysis of the impact of this process in PAA sensitivity.…”
mentioning
confidence: 99%
“…Hering et al (95) were among the first to establish a relationship between Ca 2+ channel inactivation and use-dependent Ca 2+ channel block by PAA. Since that time, single amino acids have been identified as inactivation determinants in motifs IIIS6, IVS6, and IVS5, with some of them also serving as high-affinity determinants for the DHP receptor site (94)(95)(96).…”
Section: Use Dependencementioning
confidence: 99%
“…Identical pulse protocols were used in the presence of drugs. Diltiazem (racemic) was perfused in the bath (for a 2.5-min period) at concentrations of 200 M. This concentration was selected because it provided sufficient block for the use-dependent measurements in Xenopus oocytes (13).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous finding showed that a segment in IVS5 of the human ␣ 1C (Ca v 1.2) subunit is critically involved in inactivation of the channel (13). Consequently, mutants constructed in this region lost the characteristic use-dependent block by PAA and BTZ and recovered from inactivation significantly faster after drug block compared with the wild type channel.…”
mentioning
confidence: 99%